A highly stable hole-conductor-free CsxMA1-xPbI3 perovskite solar cell based on carbon counter electrode. (1st March 2020) - Wang, Shaowei; Liu, Huijing; Bala, Hari; Zong, Beibei; Huang, Liwen; Guo, Zu-an; Fu, Wuyou; Zhang, Bo; Sun, Guang; Cao, Jianliang; Zhang, Zhanying
Abstract: Hole-conductor-free perovskite solar cells (PSCs) based on carbon counter electrode were fabricated under a high humidity air environment and the performance of Cs + doping in methylammonium lead iodide perovskite (Cs x MA1- x PbI3 ) as light absorber layer was investigated and discussed. After the doping of Cs +, the excellent morphology, crystallinity and light absorption of perovskite thin films were observed by corresponding test methods, leading to the higher short-circuit current density and open-circuit voltage in the relevant devices. However, excessive Cs + doping can damage the performance of PSCs. The optimized device with x = 0.05, exhibited open-circuit voltage of 956 mV, short-circuit current density of 21.73 mA/cm 2, fill factor of 0.509 and the power conversion efficiency ( PCE ) of 10.57% under AM 1.5G illumination showing a 16% enhancement than pure MAPbI3 devices. The PSCs based on carbon counter electrode also showed high stability, despite being stored under ambient air without encapsulation. After 1000 h, the Cs0.05 MA0.95 PbI3 devices maintained more than 90% of their initial PCE . The long-term stability can be attributed to the synergistic interaction of Cs + on the solid solution strengthening of MAPbI3 and the protection of the hydrophobic carbon electrode on the perovskite active layer.